Maternal Suicide Ideation and Behaviour During Pregnancy and the First Postpartum Year: A Systematic Review of Psychological and Psychosocial Risk Factors - Reid, Holly E.; Pratt, Daniel; Edge, Dawn; Wittkowski, Anja (Frontiers in Psychiatry, 2022)
Suicide is a leading cause of maternal death during pregnancy and up to a year after birth (perinatal period). Many psychological and psychosocial risk factors for maternal suicidal ideation and behaviour have been investigated. Despite this, there have been no attempts to systematically search the literature on these risk factors. Additionally, few studies have described how the risk factors for suicidal ideation, attempted suicides and suicide deaths differ, which is essential for the development of tools to detect and target suicidal ideation and behaviour. Seven databases were searched up to June 2021 for studies that investigated the association between suicidal ideation and/or suicidal behaviour and psychological/psychosocial risk factors in pregnant and postpartum women. The search identified 17,338 records, of which 59 were included. These 59 studies sampled a total of 49,929 participants and investigated 32 different risk factors. Associations between abuse, experienced recently or during childhood, and maternal suicide ideation, attempted suicide and death were consistently reported. Social support was found to be less associated with suicide ideation but more so with suicide attempts. Identifying women who have experienced domestic violence or childhood abuse and ensuring all women have adequate emotional and practical support during the perinatal period may help to reduce the likelihood of suicidal behaviour.